Uji Validitas Isi Booklet “The Giant Book of Emotions” untuk Meningkatkan Pemahaman Emosi pada Psikotik - Wulan Lestari; Beny Rahim; Nurul Hafizah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Individuals with psychotic disorders generally struggle to recognize and describe emotions. This is linked to alexithymia, the inability to identify and describe emotions. Understanding emotions is vital for stability and preventing relapse. Therefore, a psychoeducational booklet based on the Toronto Alexithymia Scale (TAS-20) construct was developed to improve emotional understanding in individuals with psychotic disorders.To determine the content validity value of “The Giant Book of Emotions” booklet to improve emotional understanding in psychotic individuals. This Research and Development study uses the 3D model (Define, Design, Develop). Content validity testing was conducted through expert judgment by purposively selected validators to assess aspects of material and emotional understanding sheets. Data analysis was performed using the Aiken’s V formula with descriptive analysis.This study resulted in “The Giant Book of Emotions” booklet, which consist of 8 sessions. The results of the booklet’s content validity test ranged from 0.69-0.94, falling into the high to very high category.The Giant Book of Emotions booklet, designed to enhance emotional understanding in individuals with psychotics is declared valid through the content validity testing process.